Retinal and optic nerve functions in incontinentia pigmenti: long-term elctrophysiological follow-up - janaky, Márta; Jánossy, Ágnes; Kovács, Attila; Lőrincz, Daniella; Nagy, Dóra; Török, Dóra; Benedek, György (Scandinavian Journal of Optometry and Visual Science, 2020)
Incontinentia pigmenti (IP) is a rare, X-linked, dominantly inherited disease affecting mostly females, which is best characterized as an autoimmune disease. It is a multisystem disorder affecting ectodermal tissues. Ocular abnormalities usually occur early in childhood, with subsequent retinal detachment and vision loss. Vision rarely remains intact until adulthood. We present the 17-year visual electrophysiological follow-up of such a rare patient and her mother. The mother was only a carrier, but the daughter developed various manifestations of IP. The aim of our investigations was to obtain information on the progression of functional deterioration in IP. Electroretinography (ERG), multifocal electroretinography (mfERG), visual evoked potentials (VEP), ultrasound (US) and optical coherence tomography (OCT) were performed at regular intervals between the patient’s ages of 9 and 26 years (2003 to 2020). From 9 to 22 years of age, a characteristic picture of spared vision with minimal ophthalmoscopic alterations and fluctuating ERG anomalies were observed in the left eye. It was only between the ages of 22 and 23 that subjective symptoms developed, and then complete loss of vision in the affected eye ensued rapidly. The right eye remained clinically asymptomatic throughout the observation period. The mother remained completely asymptomatic, but she showed similar ERG alterations. Electroretinography is a sensitive indicator of the activity of the ocular immune or inflammatory reactions in IP, and it readily detects their functional effect even in the absence of clinical symptoms. Thus, it is recommendable not only for the longterm functional follow-up of these patients, but probably also for early disease-specific screening. ERG recordings from the presented case suggest that the characteristic, asymmetric pattern of retinal functional involvement may be traced back to the different degrees to which the two eyes were exposed to the intermittent reactivations of the disease.